Studi Analisis tentang Inovasi dan Perubahan dalam Kebijakan Pendidikan Islam - Abdul Haris Rasyidi (PALAPA, 2016)
Innovation and change in education policy discourse that Islam is interesting to be discussed. This regard, the policy of Islamic education as the basis for the development of Islamic education, both substantive and orientatif in any educational institution in Indonesia to follow up by researchers and experts of Islamic education as a result (result) and the foundation and to look for color as well as systematic new direction in education, especially in menyonsong innovation and change in Islamic education. This brief paper seeks to examine more deeply about Islamic education policies that have been actualized in the Constitution and the regulations applicable in Islamic education.